Competition Policy for Modern Banks - Ratnovski, Lev (IMF Working Papers; Working Paper ;, 2013)
Traditional bank competition policy seeks to balance efficiency with incentives to take risk. The main tools are rules guiding entry/exit and consolidation of banks. This paper seeks to refine this view in light of recent changes to financial services provision. Modern banking is largely market-based and contestable. Consequently, banks in advanced economies today have structurally low charter values and high incentives to take risk. In such an environment, traditional policies that seek to affect the degree of competition by focusing on market structure (i.e. concentration) may have limited effect. We argue that bank competition policy should be reoriented to deal with the too-big-to-fail (TBTF) problem. It should also focus on the permissible scope of activities rather than on market structure of banks. And following a crisis, competition policy should facilitate resolution by temporarily allowing higher concentration and government control of banks.